Serum sialic acid that the value in pulmonary thromboembolism - Huseyin, Cebicci; Oguzhan, Bol; Sukru, Gurbuz; Ali, Koc; Bahar, Arslan; Taner, Sahin; Ozan, Yaman (Acta Medica Mediterranea, 2015)
Introduction: Pulmonary thromboembolism occurs mostly as a complication of deep venous thrombosis. Pulmonary embolism is the third most common cause of cardiovascular death behind coronary artery disease and stroke. Studies with sialic acid have demonstrated that there is an association between serum total sialic acid levels and cardiovascular mortality and atherosclerosis. Also, there are studies that showed increased serum total sialic acid levels in ischemic conditions such as acute myocardial infarction. We aimed to investigate whether sialic acid could be used as a marker to support or exclude a diagnosis of pulmonary embolism like D-dimer. Materials and methods: Patients 18 years of age and older who had been diagnosed with pulmonary embolism who agreed to participate the study were enrolled at the emergency room. Information about the following were recorded on the patient form: identification, sex, complaints, chest radiography findings, Wells score and Geneva score for pulmonary thromboembolism and the pulmonary vessel(s) showing evidence for embolism as detected by computed tomography thorax angiography. Forty-five subjects were concurrently enrolled as control group. Control group was selected among sex- and age-matched patients. Sialic acid levels in serum were quantified by using Enzyme-Linked ImmunoSorbent Assay technique. Results: A total of 90 subjects were enrolled in the study (patient group, n= 45 and control group, n=45). Sialic acid levels were 9.63 nmol/L (1.00-60.37) in the patient group and 2.17 nmol/L (0.93-4.38) in the control group. A statistically significant elevation was found in sialic acid levels of the patient group versus control group (p=0.03). Conclusion: In conclusion, we observed that a thrombus elicited a physiological response in patients with pulmonary thromboembolism which was similar to that occurring in the cases of acute myocardial infarction and stroke, and also pulmonary thromboembolism patients had elevated sialic acid levels.
Keywords: D-dimer; Emergency medicine; Pulmonary thromboembolism; Sialic acid